Business Group - Ventura Vega, Zaira Grimaldina (2022)
This legal article analyzes the issue of the so-called business group from a doctrinarian viewpoint, to subsequently comment on the legal-labor problems, that is, the lack of a specific legal regulation in our legal order. Selected case law is presented on this subject for a better understanding of the topic.